Investigation of eye movements of an aircraft pilot under blind approach conditions - Watts, A. F. A. (College of Aeronautics, 1955)
Eye movement patterns were obtained of a pilot in an aircraft fitted with a standard R.A.F. blind flying panel on several approaches under Standard Beam Approach conditions, These patterns were obtained by photographing the reflection of the pilot's eyes in a mirror attached to the instrument panel. The results show the 1) Proportion of time spent on each instrument, 2) Duration of the fixation time on each instrument, 3) Frequency of the eye fixations, 4) Sequence of eye movements. It was originally intended to investigate the eye movements on an I.L.S. approach using the Zero Reader and. I.L.S. Cross Pointer independently. Unforseen difficulties and delays, however, prevented the completion of this part of the investigation.